Legal Analysis of Traffic Accident Victim Media Distribution Under Article 27 Paragraph 1 of ITE Law - Pinandito, Satrio; Sriono, Sriono; Toni, Toni (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze the legal regulation of the dissemination of content containing decency in the form of spreading photos and videos of traffic accident victims according to Article 27, paragraph 1 of Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE), as well as obstacles in determining suspects in the dissemination of such content. The research uses a normative juridical approach by studying legislation, theories, and related concepts. The results show that the legal regulation of the dissemination of content containing decency is regulated in Article 27, paragraph 1 and Article 45 of the ITE Law, which states that every Person who intentionally and without properly distributes, transmits, or makes accessible electronic information or electronic documents that have content violating decency can be punished with imprisonment of up to six years and a maximum fine of Rp 1 billion. Law No. 1, the Year 2024, reaffirms this provision with additional exceptions for public interest, self-defence, or if the information is a work of art, culture, sports, health, or science. Obstacles in disclosing the perpetrators of the distribution of decency and pornography content to traffic victims include a lack of adequate human resources, limited facilities and infrastructure, and a lack of cooperation between related agencies and the community. The implications of this research indicate the need for increased legal awareness and cooperation between various parties to effectively enforce the Law related to the dissemination of decency content. In addition, increasing the capacity and resources of law enforcement officials is essential to overcome the existing obstacles.